Weak Contractions, Common Fixed Points, and Invariant Approximations - Nawab Hussain; Yeol Je Cho (Journal of Inequalities and Applications, 2009)
The existence of common fixed points is established for the mappings, where T is (f,θ,L)-weak contraction on a nonempty subset of a Banach space. As application, some results on the invariant best approximation are proved. Our results unify and substantially improve several recent results given by some authors.